Evaluación del potencial energético de la producción de biogás en el relleno sanitario del cantón salcedo durante el año 2015. Propuestas para un aprovechamiento sostenible - Albán Castellanos, Edwin Daniel (2016)
Due to the high pollution that currently exists, the human being has searched new sources of alternative energy to satisfy their needs. The sanitary landfill in Salcedo – Ecuador, it‟s place of study, due to the fact that, there is a waste of potencial energy of biogas generated. Implementing a extraction system was possible to capture an average of 4100 Standart Cubic Feet Day SCFD (116 m3 day-1). With the application of Biogas Ecuador Model developed by EPA US, for the year 2015 exist a production of biogas of 192 m3 h-1. The Chromatography of biogas shows an average of Methane (CH4) 53%, Carbon Dioxide (CO2) 43%, Nitrogen (N) 2% and other components less than 2%, with a Net Heating Value 515 BTU ft-3. With those results, it is proposed to use the resource in a system evaporation of lixiviates of 150 L h-1 of capacity as a first option. And the second proposal, to implement a power generation system of 10 kW, wich could be used for lighting the final disposal site.